DNA barcoding and phylogenetic analysis of bagrid catfish in China based on mitochondrial COI gene. (17th February 2020) - Zou, Rui; Liang, Cong; Dai, Mengmeng; Wang, Xiaodong; Zhang, Xiuyue; Song, Zhaobin
Abstract: The family Bagridae is a collection of species widely distributed in Africa and Asia with a high diversity of morphology. The species identification and phylogenetic relationship in this family have been confused and controversial. In order to explore the effectiveness of DNA barcoding in species identification of Bagridae, sequences of mitochondrial cytochrome c oxidase I (COI) gene of 20 species in four genera of Bagridae were used to analyse barcoding gap and to reconstruct phylogenetic relationship. Both the barcoding gap and the phylogenetic tree analysis showed that the COI gene-based DNA barcoding is an effective molecular technique for most species recognition of Chinese Bagridae. However, the rapid speciation and incomplete lineage sorting may affect the accuracy of DNA barcoding in species identification in certain species, and adding additional genes, such as nuclear gene, may help to achieve accurate identification of these species. The phylogenetic tree showed that the monophyly of genera Pelteobagrus, Leiocassis and Pseudobagrus did not exist, which supports that the species of genera Pelteobagrus, Pseudobagrus and Leiocassis distributed in China should be revised into one genus.